2022
DOI: 10.47748/tjvr.993547
|View full text |Cite
|
Sign up to set email alerts
|

Invastigation of 16S rRNA, mecA and nuc genes in coagulase-positive and negative Staphylococci by Real-Time PCR

Abstract: Objective: Staphylococcus aureus is a Gram-positive and round-shaped bacterium. It is often positive for catalase and nitrate reduction. Pathogenic isolates support infections by producing protein toxins and the expression of a cell-surface protein virulence factors. Sepsis-related to methicillin-resistant S. aureus (MRSA) has significant morbidity and high mortality rates (15-30%). The methicillin resistance for S. aureus is coded with the MecA gene, while the methicillin sensitivity is coded with the Nuc gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
0
1
Order By: Relevance
“…The PCR study of mecA genes (encoding methicillin resistance) and nuc genes (encoding staphylococcal thermostable nuclease) is considered a quick MRSA strain identification approach (Sahebnasagh et al, 2014). The 23S rRNA gene was found in 100% of the S. aureus isolates in this study, which was similar to recent findings from Turkey (Aksakal et al, 2022) and India (Murugadas et al, 2016). The nuc gene was detected in 80% of screened S. aureus isolates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The PCR study of mecA genes (encoding methicillin resistance) and nuc genes (encoding staphylococcal thermostable nuclease) is considered a quick MRSA strain identification approach (Sahebnasagh et al, 2014). The 23S rRNA gene was found in 100% of the S. aureus isolates in this study, which was similar to recent findings from Turkey (Aksakal et al, 2022) and India (Murugadas et al, 2016). The nuc gene was detected in 80% of screened S. aureus isolates.…”
Section: Discussionsupporting
confidence: 91%
“…The highest prevalence (100%) was earlier reported in India (Murugadas et al, 2016), and prevalence of 90% and 100% was reported in Egypt (Elkamouny et al, 2020;Anjusha et al, 2022, respectively), whereas the lowest prevalence (14.43% and 60%) was reported by prior studies on S. aureus isolated from fish (Mohammed et al, 2020;Aksakal et al, 2022, respectively). With regard to our finding, the prevalence of mec gene (60%) was higher than those in prior studies that reported prevalence of 44% (Elkamouny et al, 2020), 10.30% (Mohammed et al, 2020), 47.5% (Aksakal et al, 2022), and 1.8% (Anjusha et al, 2022) in S. aureus isolated from fish but lower than the 100% reported in India (Murugadas et al, 2016).…”
Section: Discussioncontrasting
confidence: 76%